THE POISON DIARY OF 1995 Part - 2 - Abd Razak, Dzulkifli (1996)
In the second half of 1995, poisoning tragedies continued unabated. The next part of the Poison Diary of 1995 notes a larger number of poisonrelated incidents involving the environment, especially at the international level. July In Terengganu, a food poisoning case involving 173 female hostel residents was reported after they had consumed hostel canteen food were. More than 50 of them were treated for food poisoning at the local hospital. Meanwhile, a study revealed that Cameron Highland had one of the highest suicide rates in the world. The main factor was allegedly the availability of concentrated pesticides. Enforcement on drinkdriving began on July 1 in the Klang Valley. The law against drinkdriving comes under the Road Transport Act 1987 passed by the parliament in 1993. In their first week of its enforcement, the police booked more than 50 motorists for driving under the influence of alcohol. Offenders can be fined up to RM2,000 or face a maximum jail sentence of six months.